SISTEM INFORMASI PENILAIAN KINERJA PEGAWAI BERBASIS WEB SEBAGAI SOLUSI DIGITALISASI SDM - Kartikasari, Meivi; Syntia Widyayuningtias Putri Listio; Bagus Kristomoyo Kristanto; Mahdi Bashroni Rizal (CYBERSPACE: Jurnal Pendidikan Teknologi Informasi, 2026)
Employee performance assessment is a critical component of human resource management in any organization. However, many organizations still rely on conventional spreadsheet-based methods that result in calculation errors, delayed reporting, subjective evaluations, and data manipulation risks. This study presents the development of a web-based employee performance assessment information system using PHP and MySQL. The system accommodates three user roles: administrator, assessor, and employee. Black box testing across sixteen functional scenarios confirmed that all system features operated successfully. The system provides standardized evaluation criteria, automated scoring, real-time reporting, and centralized data storage, significantly improving objectivity, efficiency, and accountability in performance assessments.